Central and autonomic system signs with in utero drug exposure. Issue 2 (1st September 2002) - Bada, H S; Bauer, C R; Shankaran, S; Lester, B; Wright, L L; Das, A; Poole, K; Smeriglio, V L; Finnegan, L P; Maza, P L
Abstract : Aims: To determine risk for central nervous system/autonomic nervous system (CNS/ANS) signs following in utero cocaine and opiate exposure. Methods: A multisite study was designed to determine outcomes of in utero cocaine and opiate exposure. A total of 11 811 maternal/infant dyads were enrolled. Drug exposed (EXP) infants were identified by maternal self report of cocaine or opiate use or by meconium testing. Of 1185 EXP, meconium analysis confirmed exposure in 717 to cocaine (CO) only, 100 to opiates (OP), and 92 to opiates plus cocaine (OP+CO); 276 had insufficient or no meconium to confirm maternal self report. Negative exposure history was confirmed in 7442 by meconium analysis and unconfirmed in 3184. Examiners masked to exposure status, assessed each enrolled infant. Using generalised estimating equations, adjusted odds ratios (OR) and 95% confidence intervals (CI) were estimated for manifesting a constellation of CNS/ANS outcomes and for each sign associated with cocaine and opiate exposure. Results: Prevalence of CNS/ANS signs was low in CO, and highest in OP+CO. Signs were significantly related to one another. After controlling for confounders, CO was associated with increased risk of manifesting a constellation of CNS/ANS outcomes, OR (95% CI): 1.7 (1.2 to 2.2), independent of OP effect, OR (95% CI): 2.8 (2.1 to 3.7). OP+CO had additive effects, OR (95% CI): 4.8 (2.9 to 7.9). Smoking also increased the risk for the constellation of CNS/ANS signs, OR (95% CI) of 1.3 (1.04 to 1.55) and 1.4 (1.2 to 1.6), respectively, for use of less than half a pack per day and half a pack per day or more. Conclusion: Cocaine or opiate exposure increases the risk for manifesting a constellation of CNS/ANS outcomes.